Clinical supervisors' experience of giving feedback to students during clinical integrated learning. (2nd January 2022) - Sellberg, Malin; Skavberg Roaldsen, Kirsti; Nygren-Bonnier, Malin; Halvarsson, Alexandra
ABSTRACT: Background : For students within health-care education, clinical integrated learning has an important role in combining theory and practice. Constructive feedback is a cornerstone of effective clinical teaching, even though it can be a challenging task for both students and supervisors. There are limited studies on clinical physiotherapists' experience of giving feedback to students. Purpose : To explore clinical physiotherapy supervisors' experience of giving feedback to students during clinical integrated learning. Method : Twelve physiotherapists were interviewed in focus groups about their experiences of giving feedback to students. The interviews were analyzed using qualitative content analysis. Results : One latent, overarching theme was identified, which was continuous development and support within the social network at the workplace facilitates the work of giving feedback to students and three manifest main themes: (1) constructive dialog; (2) professionalism; and (3) enabling strategies. Conclusion : The current study focuses on supervisors' experiences of giving feedback to students in a clinical setting. The findings showed that giving feedback to students was a part of continuous development, facilitated by the social network at the workplace, and that the supervisors aimed to be professional while handling emotions in social interactions between supervisors and students.